Distinguishing the contributions of neuronal and mucosal serotonin in the regulation of colonic motility. Issue 8 (21st March 2022) - Martin, Alyce M.; Jones, Lauren A.; Wei, Lai; Spencer, Nick J.; Sanders, Kenton M.; Ro, Seungil; Keating, Damien J.
Abstract: Background: Specialized enterochromaffin (EC) cells within the mucosal lining of the gut synthesize and secrete almost all serotonin (5‐hydroxytryptamine, 5‐HT) in the body. Significantly lower amounts of 5‐HT are made by other peripheral tissues and serotonergic neurons within the enteric nervous system (ENS). EC cells are in close proximity to 5‐HT receptors in the ENS, and the role of 5‐HT as a modulator of gut motility, particularly colonic motor complexes, has been well defined. However, the relative contribution of neuronal 5‐HT to this process under resting and stimulus‐evoked conditions is unclear. Methods: In this study, we combined the use of the selective serotonin transporter (SERT) inhibitor, fluoxetine, with two models of mucosal 5‐HT depletion—surgical removal of the mucosa and our Tph1 Cre/ERT2 ; Rosa26 DTA mouse line—to determine the relative contribution of neuronal and mucosal 5‐HT to resting and distension‐evoked colonic motility. Key results: Fluoxetine significantly reduced the frequency of colonic migrating complexes (CMCs) in flat‐sheet preparations with the mucosa present and in intact control Tph1‐DTA colons in which EC cells were present. No such effect was observed in mucosa‐free preparations or in intact Tph1‐DTA preparations lacking EC cell 5‐HT. Conclusions and inferences: We demonstrate that mucosal 5‐HT release plays an important role in distension‐evoked colonic motility, and that SERT inhibition no longer alters gut motility when EC cells are absent, thus demonstrating that ENS 5‐HT does not play a role in regulating gut motility. Abstract : Specialized serotonin (5‐HT)‐producing enterochromaffin (EC) cells lining the gut wall synthesis and secrete almost all 5‐HT in the body, with much smaller amounts produced by neurons within the enteric nervous system (ENS). Gut 5‐HT has a significant role in regulating intestinal motility patterns; however, it is unclear whether EC cell‐derived or neuron‐derived 5‐HT is the major contributor to regular motility patterns in the colon. In this study, we used the selective serotonin reuptake inhibitor, fluoxetine, to inhibit the reuptake of 5‐HT via SERT channels, whereby increasing the pool of available 5‐HT at synaptic terminals in ex vivo colon preparations from mice. This allowed us to assessed the relative contribution of 5‐HT coming from either (A) EC cells or (B) the ENS to the regulation of normal gut motility patters in the colon. Our major finding from this study was that fluoxetine decreased colonic motility only when mucosal EC cells were present, highlighting that EC cell‐derived 5‐HT is the major contributor to colonic motility patterns, while release of neuronal 5‐HT at synaptic terminals does not appear play a role in regulating GI motility.